Functional analysis of a vacuolar ABC transporter in wild-type Candida albicans reveals its involvement in virulence - Theiß, Stephanie; Kretschmar, Marianne; Nichterlein, Thomas; Hof, Herbert; Agabian, Nina; Hacker, Jörg; Köhler, Gerwald A. (Molecular microbiology, 2002)
ATP-driven transport proteins belonging to the ATP-binding cassette (ABC) superfamily perform important functions in cell metabolism and detoxification. Compounds can be actively transported across membranes, including the plasma membrane or organellar membranes. The vacuole is an important organelle in fungal cells required for compartmentalization of metabolites as well as toxic substances. Sequestration into the vacuole is often energy-dependent. We present the first isolation and molecular analysis of a vacuolar ABC transporter gene in the opportunistic fungal pathogen Candida albicans. The protein encoded by the MLT1 gene is highly similar to Multiple Drug Resistance-associated Protein (MRP)-like transporters of yeast and higher organisms that form the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR)/MRP subfamily of ABC transporters, a class of proteins so far not characterized in C. albicans. MLT1 expression is extensively growth phase-regulated, and gene transcripts are inducible by metabolic poisons. Gene replacement mutants generated in wild-type C. albicans with the dominant selection marker MPAR showed a profound reduction in virulence in a mouse peritonitis model that was reversed by complementation with an intact MLT1 gene. Hence, this report provides primary evidence for the involvement of vacuolar ABC transporters in fungal virulence.